Water, wastewater, and stormwater infrastructure management. - Grigg, Neil S. (CRC Press ; IWA Publishing, 2012)
Urban water services are building blocks for healthy cities, and they require complex and expensive infrastructure systems. Most of the infrastructure is out of sight and tends to be taken for granted, but an infrastructure financing crisis looms in the United States because the systems are aging and falling behind on maintenance. A road map for public works and utility professionals, Water, Wastewater, and Stormwater Infrastructure Management, Second Edition provides clear and practical guidance for life-cycle management of water infrastructure systems. Grounded in solid engineering and busin.